A case of metastatic malignant granular cell tumour of the scalp. Issue 4 (24th April 2021) - Williams, Geoffrey; Neblett, Carlos; Warren, Shereika; Blake, Garfield
Abstract: Granular cell tumours of the scalp are rare. Malignant transformation of these tumours is even more uncommon, making the diagnosis exceedingly difficult. The recommended treatment of surgical excision with negative margins is not easily achieved in this location, given the anatomy of the scalp.